2012
DOI: 10.1159/000339607
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal Goblet Cell Carcinoid Tumour: A Case of Unexpected Lung Metastasis

Abstract: Goblet cell carcinoid tumours are often considered a subset of appendiceal neuroendocrine tumours which behave more aggressively. They usually metastasize through transcoelomic/peritoneal invasion and common sites include the ovaries, peritoneum, and liver. Metastases may have goblet cell carcinoid, signet ring cell carcinoma or classic carcinoid histology. We report the first case in the literature of a patient with a goblet cell carcinoid with lung metastasis, which was associated with unfavourable outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results of immunohistological examination using the Ki-67 proliferative index are not always reliable for assessment of the aggressive behavior of tumors. Pericleous et al 22 reported a case of GCC with lung metastasis and a Ki-67 proliferative index of less than 5%. In four cases of metastasis to lymph nodes and distant metastasis identified in the present study, the Ki-67 proliferative index ranged from 20% to 70%.…”
Section: Discussionmentioning
confidence: 99%
“…The results of immunohistological examination using the Ki-67 proliferative index are not always reliable for assessment of the aggressive behavior of tumors. Pericleous et al 22 reported a case of GCC with lung metastasis and a Ki-67 proliferative index of less than 5%. In four cases of metastasis to lymph nodes and distant metastasis identified in the present study, the Ki-67 proliferative index ranged from 20% to 70%.…”
Section: Discussionmentioning
confidence: 99%